1990
DOI: 10.1093/ije/19.2.380
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Postmortem Interviews to Ascertain Selected Causes of Death in Children

Abstract: In developing countries, diagnoses of diseases associated with deaths in children are frequently derived from retrospective maternal interviews. To determine the validity of this methodology, and to define sensitive and specific diagnostic algorithms, we compared symptoms and signs reported by mothers using structured questionnaires, with selected physician diagnoses for 164 deaths among hospitalized children on the Philippine island of Cebu. The 164 decreased children had 256 physician diagnoses of acute lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0
5

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(81 citation statements)
references
References 0 publications
3
73
0
5
Order By: Relevance
“…Sevt t eral studies suggest that wellttrained lay people can obtain accurate information when using culturally and linguistically appropriate questionnaires. 18,21,22 Large numbers of interviewers may produce diverse results, and the interviewer's gender and ethnic background in relat t tion to respondents can also influence the outcome. 20 The choice of interviewer should be adapted to the local commut t nity, but the characteristics and training of interviewers used in various sites should be standardized.…”
Section: Interviewersmentioning
confidence: 99%
See 2 more Smart Citations
“…Sevt t eral studies suggest that wellttrained lay people can obtain accurate information when using culturally and linguistically appropriate questionnaires. 18,21,22 Large numbers of interviewers may produce diverse results, and the interviewer's gender and ethnic background in relat t tion to respondents can also influence the outcome. 20 The choice of interviewer should be adapted to the local commut t nity, but the characteristics and training of interviewers used in various sites should be standardized.…”
Section: Interviewersmentioning
confidence: 99%
“…The validity of physician review of VA has been tested in children and adults, and shown to have reasonable sensitivity and specificity for selected causes of death. 2,11,14,17,21,22,[25][26][27] However, the repeatability of causes of death derived by physician review is low. 28 Although intertobserver agreement is shown to be high in some studies, this may simply reflect consistency in physicians' prior knowledge of the local epidemiology.…”
Section: Analytical Challenges Deriving Causes Of Death From Verbal Amentioning
confidence: 99%
See 1 more Smart Citation
“…Verbal autopsy is a method of assessing the cause of death based on an interview with the next of kin or other caregivers who were present at the time of death or who are knowledgeable about the events leading up to the death. Verbal autopsies have been used previously in Bangladesh to provide important data on causes of child death (Chen et al, 1980;Zimicki et al, 1985;D'Souza, 1985;Bhatia, 1989;Fauveau et al, 1994;Snow et al, 1992;Kalter et al, 1990;Kamal et al, 1989;Salway et al, 1994;Baqui et al, 1998). …”
Section: High-risk Fertility Behaviormentioning
confidence: 99%
“…Somente em 2001, 54% da mortalidade infantil mundial pôde ser atribuída, direta ou indiretamente, à desnutrição (WHO, 2007). A principal causa de morte de desnutridos está associada a doenças infecciosas, sendo a pneumonia e a diarréia as mais freqüentes (KALTER et al, 1990). A desnutrição em si é capaz de desencadear doenças devido à supressão da função do sistema imunológico (CUNHA et al, 2003;KEUSCH, 2003).…”
Section: Desnutriçãounclassified